Physical treatment of high EPA Yarrowia lipolytica biomass increases the availability of n‐3 highly unsaturated fatty acids when fed to Atlantic salmon. (2nd September 2013) - Berge, G.M.; Hatlen, B.; Odom, J.M.; Ruyter, B.
Abstract: A strain of Yarrowia lipolytica engineered to produce high levels of eicosapentaenoic acid (EPA) was used as feed ingredient to Atlantic salmon ( Salmo salar L.). The study was designed to investigate the effect of washing and cell disruption, on growth, bioavailability, and fillet composition of Atlantic salmon growing from 0.5 to 1 kg. Four diets containing 200 g kg ‐1 yeast (Unwashed/Not disrupted, Unwashed/Disrupted, Washed/Undisrupted, Washed/Disrupted) were compared to a fishmeal‐based control diet in a 112‐day feeding experiment. Final weights and growth rates were similar for all dietary groups. Apparent lipid digestibility was highly affected by disruption of the yeast biomass. Disruption increased the apparent digestibility of EPA from 32% to 76% in washed biomass, and from 26% to 76% in Unwashed biomass. Sum n‐3 fatty acids deposited in whole body was similar in fish fed the control diet and the diets with Disrupted yeast biomass, while fish fed Undisrupted biomass had significantly lower content of n‐3. Removal of residual medium components by washing had no discernible effect on utilization of EPA. Evidence for conversion of EPA to DHA (docosahexaenoic acid) in the fish was indicated by deposition ratio Rd < 1 for EPA and Rd > 1 for DHA.